Faktor dan Risiko Produksi Usahatani Padi Sawah Tadah Hujan Sulawesi Selatan - Arifin Arifin; La Sumange; Muhammad Arsyad Biba; Muhammad Natsir; Sri Mardiyati; Muhammad Arifin Fattah (Fakultas Pertanian, Universitas Timor, 2023)
The production process can run if the required production factor requirements have been met. Factors of production are inputs and are an absolute thing because the production process to produce a product requires a certain number of factors of production. The production process demands to be the ability to analyze and combine various factors of production to produce a certain number of products as efficiently as possible. The risk of agricultural production is greater than the risk of non-agriculture because agriculture is strongly influenced by nature such as weather, pests and diseases, temperature, drought, and flooding. The purpose of this study was to analyze the factors that influence the production of rainfed lowland rice farming and to analyze the production risks of rainfed lowland rice farming. The research locations were chosen purposively, namely Pangkep Regency and Maros Regency. The total population of the study was 1,034 people, while the number of samples of farmers who were used as respondents was 100 people. To get the number of samples used the multi-stage cluster random sampling technique. The data analysis method used was multiple linear regression analysis and quantitative descriptive. The results showed that land area, number of seeds, amount of urea fertilizer, and amount of pesticides affected the production of rainfed lowland rice farming. The production risk of rainfed lowland rice farming in Maros and Pangkep regencies is risky. Maros Regency is greater than that Pangkep Regency.